Students’ attitude towards assessment, its relation with their academic achievement, and factors that shape their attitude - Al Azad, Ahmad Ullah; Ahsan, Sumera; Mahdi, Shafi Md. (International Journal of Evaluation and Research in Education (IJERE), 2025)
Student assessment is a crucial part of the teaching-learning process that shapes students’ learning. Students’ attitudes towards assessment play an important role in determining how actively they will participate in assessment activities. It also involves exploring the complex interplay between students’ expectations and experiences regarding assessment. Therefore, this study aims to explore Bangladeshi tertiary level students’ attitude towards assessment, its relation with their academic achievement, and factors shaping their attitude. A sequential mixed-method design was employed. A total of 162 graduate and undergraduate students were surveyed with a scale to measure their attitude. Based on the attitude score, six students were interviewed for deeper insights. The findings show that students generally have a neutral attitude toward their institution’s assessment system. Among different types of assessments, students showed the most positive attitude towards classroom assessment. There is a positive but weak relationship between attitude towards assessment and students’ academic achievement. The interviews revealed that because of the subjective experience of assessment, the same assessment activities could yield different attitudes towards assessment among students. The study will provide insights into how students’ experiences with assessment contribute to developing their attitude towards assessment in an educational setting. This study may also help policy makers and educators to develop a student friendly assessment system in higher education.